The impact of Technological development on the Growth of the manufacturing sector in gulf cooperation council countries - Almaiman, Razan Mansour Hassan; Nasrulddin, Vivian Mohammed Saleh (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed at measuring the impact of technological development on manufacturing in the Gulf Cooperation Council (GCC) countries during the period (2000-2022), and that’s through the use of Panel Data (Time Series Methodology)to analyze the relation between manufacturing industries-expressed by industrial value added as an independent variable-and the indicators of technological development advancements as an independent variables- represented in the following: a number of scientific and technical journal articles, manufacturing exports, information and communications technology imports and technological industries. Study samples were gathered from 6 different countries from GCC. Six countries were: Saudi Arabia - United Arab Emirates- Bahrain - Kuwait- Oman and Qatar. The results showed that the model of fixed effects was the best for this study and through the analytical program E-Views; as expected the study concluded a direct relationship between exported manufactures and industrial value added; and unlike to expected, the study showed inverse relationship between industrial value added and both of a number of scientific and technical journal articles and industrial technologies.The study also showed that industrial value added isn’t affected by information and communications technology imports. Finally, the study presented several recommendations: the necessity of promoting investments in research and developments, supporting entities interested in technological transformation, promoting investments in the manufacturing sector, in addition to promoting partnership with leading industrial sectors.